The Influence of Principal Academic Supervision and Work Motivation on State High School Teacher Performance in Toba Regency - Hutauruk, Lenny M; Panjaitan, Binur Panjaitan; Sitompul, Baginda (JUPE : Jurnal Pendidikan Mandala, 2024)
The purpose of this research is 1) to analyze the influence of the Principal's academic supervision on the performance of State High School teachers in Toba Regency; 2) to analyze the influence of work motivation on the performance of State High School teachers in Toba Regency; 3) to analyze the influence of the principal's academic supervision and work motivation on the performance of State High School teachers in Toba Regency. The method used in this research is a quantitative research method. The population is all state high school teachers in Toba Regency, totaling 416 people and a sample of 84 people was determined, which is 20% of the total population. Data was collected using a closed questionnaire with 65 items. The results of data analysis show that: 1) the calculated F value > F table between the Principal's academic supervision on teacher performance is 22.590 > 3.15, so it is known that there is an influence of the Principal's academic supervision on the performance of State High School teachers in Toba Regency, namely 21, 6%, 2) calculated F value > F table between work motivation and teacher performance, namely 44.658 > 3.15, thus it is known that there is an influence of work motivation on the performance of State High School teachers in Toba Regency, namely 35.3%, 3) F value calculate > F table between the principal's academic supervision and work motivation on teacher performance, namely 25.298 > 3.15, thus it is known that there is an influence of the principal's academic supervision and work motivation on the performance of State High School teachers in Toba Regency, namely 38.4%. Ha is accepted and H0 is rejected.